Paper 01: ACL Reconstructed Knees Had Significantly Higher MR T1ρ and T2 Values in Cartilage but not in Meniscus Compared to Contralateral Knees at 10 Years after ACL Reconstruction. Issue 7 (30th July 2022) - Xie, Dongxing; Murray, John; Lartey, Richard; Gaj, Sibaji; Kim, Jeehun; Eck, Brendan; Winalski, Carl; Altahawi, Faysal; Jones, Morgan; Huston, Laura; Harkins, Kevin; Merrin, Lindsay; et al.
Objectives: Patients with anterior cruciate ligament (ACL) injury are at high risk for the development of post-traumatic osteoarthritis (PTOA), despite ACL reconstruction (ACLR). ACL injuries are frequently associated with damage of other structures within the knee, such as the meniscus. The meniscus is an important structure that provides protection for articular cartilage and stabilization of the joint. Long-term studies of PTOA after ACLR mainly used radiographs. Conventional magnetic resonance imaging (MRI) has been used in a limited number of studies to evaluate structural damages, but this only provides information on morphologic changes that occur at relatively late stages of the disease. In this study, we aim to use quantitative MRI (qMRI) to evaluate cartilage and meniscus degeneration in patients at 10 years after ACLR. Methods: This is a multi-site multi-vendor study that involves three sites and two MR platforms (Siemens 3T and Philips 3T). MRI protocols have been harmonized between sites and cross validation data were collected using phantoms. The patients are from a nested cohort within Multicenter Orthopaedic Outcomes Network (MOON) Onsite Cohort at 10 years after ACLR. Inclusion/Exclusion criteria were: 22-50 years old; ACL tear during a sport; no previous knee injury; no graft rupture during follow-up. In this preliminary report, 51 patients (age 32.8 ± 6.4 years; 25 females; body mass index [BMI] 25.7 ± 5.7 kg/m2; 40 hamstring autograft, 9 bone-patellar tendon-bone autograft, and 2 allograft) and 17 healthy control participants (age 30.8 ± 7.8 years; 10 females; BMI 23.8 ± 5.6 kg/m 2 ) were studied. The MRI protocol included high-resolution Dual-Echo Steady State (DESS), and combined gradient echo MAPSS T1ρ and T2 mapping. Cartilage and meniscus were automatically segmented on DESS images using an in-house developed deep-learning model into medial/lateral femoral condyle (MFC/LFC), medial/lateral tibia (MT/LT), trochlear (TRO), and patellar cartilage (PAT), and medial and lateral menisci (MM/LM). Each cartilage compartment was further divided into sub-regions based on a modified MRI Osteoarthritis Knee Score (MOAKS) definition: central and posterior for MFC/LMC (cMFC/cLMC, pMFC/pLMC); anterior, central, and posterior for MT/LT (aMT/aLT, cMT/cLT, pMT/pLT); medial, central, and lateral for PAT/TRO (mPAT/mTRO, cPAT/cTRO, lPAT/lTRO). Menisci were further divided into anterior horn (aMM, aLM), central (body) (cMM, cLM), and posterior horn (pMM, pLM) subregions. These cartilage and menisci subregions were then transformed and overlaid onto the T1ρ and T2 parameter maps after co-registering the DESS image to the first echo of the 3D MAPSS sequence using the Elastix toolbox. T1ρ and T2 parameter maps were obtained by a voxel-wise two-parameter monoexponential fitting. The mean and standard deviation for each subregion was recorded and compared between three knee groups: operated and contralateral knees from patients, and control knees from healthy controls, using a mixed-effects regression model, adjusted for age, sex, and BMI. Results: For cartilage, compared to contralateral knees, operated knees in patients had significantly higher T1ρ and T2 values in MFC, MT, and TRO compartments. Looking into subcompartments, for MFC, MT, and TRO, most of the subcompartments (cMFC, pMFC; cMT, pMT; mTRO, cTRO) showed significantly higher T1ρ and T2 values compared to contralateral knees. For LFC and LT, only the posterior subcompartments showed significantly higher T1ρ and T2 values compared to contralateral knees. For PAT, no significant differences were observed between operated and contralateral knees. Compared to healthy control knees, operated knees in patients had significantly higher T1ρ and T2 values in all the six compartments. Besides, contralateral knees also showed higher T1ρ and T2 values in LFC, LT and PAT compartments compared to healthy control knees (Figure 1 for T1ρ, T2 with similar trend was not shown). For meniscus, no significant differences in T1ρ and T2 values were observed between injured and contralateral knees. Compared to healthy control knees, both operated and contralateral knees in patients had significantly higher T1ρ values in LM and significantly higher T2 values in MM (Figure 2). Conclusions: Cartilage T1ρ and T2 values were higher in operated knees compared to contralateral knees at 10 years after ACLR, except for patellar compartment. In patellar cartilage, no significant differences were observed between sides in patients, but both sides were significantly higher than control knees. Our data showed that contralateral knees after ACLR may not represent 'healthy controls' as there might be compensatory changes and early degeneration in contralateral knees as a result of injury and surgery to their other knee. Although we observed this general trend of higher cartilage T1ρ and T2 values in the operated knees compared to contralateral knees, no significant differences were observed in meniscus T1ρ and T2 values between sides in patients, suggesting the timing of cartilage and meniscus degeneration may be different for patients after ACLR. Meniscus T1ρ and T2 values in both sides are higher than control knees, suggesting early degeneration in meniscus in patients in both sides. The results will be confirmed with more patient data being collected in the ongoing study. The relationship between qMRI, morphological tissue changes, and patient-reported outcomes after ACLR will also be evaluated in future work. Figure 1. T1p comparisons of cartilage among operated, contralateral, and healthy control knees. *P < 0.05, **P < 0.01. ***P < 0.001. Figure 2. T1p and T2 comparisons of menisci among operated, contralateral, and healthy control knees. *P < 0.05. **P < 0.01. ***P < 0.001.